PRINCIPAL COMPONENT FACTOR ANALYSIS OF CONSTRAINTS FACED BY RICE FARMERS TO ACCESSED MICRO CREDIT IN MAKURDI LOCAL GOVERNMENT AREA OF BENUE STATE, NIGERIA - Ogah, O. M.; Ochalibe, A.I.; Igbaruma, V. K. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study analyzed the constraints faced by rice farmers in their quest to access micro credit in Makurdi Local Government Area of Benue State, Nigeria. A total of 120 respondents were selected for the study using multistage sampling procedures. Primary data were collected with the use of structured questionnaire. Principal component analysis was employed as the tool of analysis for the study. Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy was 0.853 which is adequate and acceptable based on the KMO classification. The Bartlett’s test of sphericity (???? 2 = 250.34) was also significant at p < 0.01 probability level. The constraints that load high in factor one comprised of too many forms to fill (0.8512), long period of processing loan applications (0.8911), cumbersome loan application procedure (0.9133). Problem of getting guarantor (0.8211), Problem of getting collateral (0.8614) and small amount of loan (could be related to eligibility criteria or perceived risk) (0.7835) were loaded in factor 2 as serious constraints. High interest rate (0.8531) and short repayment periods (0.8742) were major challenges in factor 3. Unfavorable loan terms and repayment conditions significantly deter rice farmers from accessing credit. Constraints like high transport cost to and from loan source (0.8822) and long distance from house to loan source (0.9014) constituted serious concerns in factor 4 loading. The findings revealed these constraints hindered credit access for rice farmers. The study concluded that microcredit could play a crucial role in enhancing rice productivity in the area but with great bottlenecks. Based on these findings, government should consider reducing interest rates to improve microcredit accessibility. Encouraging the formation of well-managed cooperatives can facilitate access to credit. Collaborations between microfinance institutions and farmer cooperatives could streamline loan distribution.